Obstacles and Solutions in Islamic Religious Education Learning: Case Study at Al Fajar Maleber Islamic Middle School - Romi Maulana; Siti Aripah; Siti Rubaiah; Euis Latipah (Kasyafa: Jurnal Pendidikan Agama Islam, 2025)
This study aims to reveal and analyze the various obstacles that arise in the learning process of Islamic Religious Education (PAI) at the Junior High School (SMP) level, as well as formulate appropriate solutions to overcome them. The approach used is descriptive qualitative, with data collection techniques through interviews, observation, and documentation. The research findings show that the main challenges in PAI learning include low student motivation, limited technology facilities, lack of parental involvement, and teachers' difficulties in adjusting learning methods to the characteristics of today's students. However, this study also identified a number of solutions that can be applied, including understanding individual student characteristics and needs, applying innovative approaches, utilizing educational technology media to create a more interesting and interactive learning atmosphere, and consistently giving appreciation to students to increase their motivation. Support from the school and good collaboration with parents are also important factors in supporting the success of PAI learning. This study recommends that schools strengthen technology facilities and organize training for teachers to be more proficient in using technology-based learning media. In addition, it is necessary to build closer cooperation between teachers and students, schools, parents, and the surrounding community to create a conducive learning environment. With these steps, it is expected that the PAI learning process at Al Fajar Islamic Junior High School in Maleber can take place more effectively and have a positive impact on strengthening students' religious values.